2022
DOI: 10.1038/s41598-022-15033-9
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of 1,25(OH)2D3 in clinical and experimental kidney disease

Abstract: Chronic kidney disease (CKD) results in calcitriol deficiency and altered vitamin D metabolism. The objective of this study was to assess the 24-hydroxylation-mediated metabolism of 25(OH)D3 and 1,25(OH)2D3 in a cross-sectional analysis of participants with a range of kidney function assessed by precise measured GFR (mGFR) (N = 143) and in rats with the induction and progression of experimental kidney disease. Vitamin D metabolites were assessed with LC–MS/MS. Circulating measures of 24-hydroxylation of 25(OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…the animal. Later in vitro studies by Inouye and Sakaki (26) and Tang et al (27) explored the catalytic properties of the 1-hydroxylase enzyme and confirmed that 1,24,25-(OH) 3 (29) It should be noted that the renewed interest in the catabolite 1,24,25-(OH) 3 D 3 is not confined to its role in bone metabolism but is also implicated in the dysfunctional metabolism in chronic kidney disease (30,31) as well as in normal neonatal calcium homeostasis and skeletal development. (32) Although 1,25-(OH) 2 D 3 is considered the active form of vitamin D, the other metabolites measured in this study possess VDR binding capabilities and actions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…the animal. Later in vitro studies by Inouye and Sakaki (26) and Tang et al (27) explored the catalytic properties of the 1-hydroxylase enzyme and confirmed that 1,24,25-(OH) 3 (29) It should be noted that the renewed interest in the catabolite 1,24,25-(OH) 3 D 3 is not confined to its role in bone metabolism but is also implicated in the dysfunctional metabolism in chronic kidney disease (30,31) as well as in normal neonatal calcium homeostasis and skeletal development. (32) Although 1,25-(OH) 2 D 3 is considered the active form of vitamin D, the other metabolites measured in this study possess VDR binding capabilities and actions.…”
Section: Discussionmentioning
confidence: 96%
“…( 28 ) In support of the possibility that circulating 1,24,25‐(OH) 3 D 3 could be derived from CYP27B1 hydroxylation of high levels of circulating 24,25‐(OH) 2 D 3 , Martineau et al demonstrated increased 1,24,25‐(OH) 3 D 3 (without an increase in 1,25‐[OH] 2 D 3 ) in response to pharmacological doses of 24,25‐(OH) 2 D 3 given to mice undergoing bone fracture repair. ( 29 ) It should be noted that the renewed interest in the catabolite 1,24,25‐(OH) 3 D 3 is not confined to its role in bone metabolism but is also implicated in the dysfunctional metabolism in chronic kidney disease ( 30,31 ) as well as in normal neonatal calcium homeostasis and skeletal development. ( 32 )…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in CYP27B1 activity occurs in kidney disease, which subsequently inhibits the production of 1,25(OH) 2 D 3 and impairs the reabsorption of 25(OH)D [ 1 ]. A significant decrease in 1,25(OH) 2 D 3 levels is observed when the GFR is 40 mL/min or less [ 33 , 34 ]. The decrease in CYP27B1 enzyme activity and 1,25(OH) 2 D 3 levels can be explained by the increase in FGF-23 activity observed in the early stages of kidney disease [ 35 , 36 ].…”
Section: Vitamin D Signaling Pathway In Diabetic Kidney Diseasementioning
confidence: 99%
“…Furthermore, the goal should not be complete normalization of iPTH levels. New developments, such as extended-release formulations [ 109 , 110 ] (which correct both vitamin D deficiency and are more effective than native in decreasing iPTH levels) and new analogs, biomarkers, molecular targets, and even renal pathologies [ 111 , 112 , 113 , 114 , 115 , 116 , 117 ], may then help us better define optimal VD and iPTH levels or the best formulation at different CKD stages [ 92 , 107 , 109 ], thereby directing us towards an improved, personalized medicine. It is possible that the approaches that we took to correct VD deficiency are at least partially wrong and that current interventions with native and/or active VD were not properly targeted at more effective goals.…”
Section: Kdigo Guidelines: Secondary Hyperparathyroidism and Active V...mentioning
confidence: 99%